2012
DOI: 10.1007/s13312-012-0129-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deworming vs Iron-Folic acid supplementation plus deworming on growth, hemoglobin level, and physical work capacity of schoolchildren

Abstract: The effect of deworming vs deworming and weekly Iron-Folic acid (IFA) on growth, hemoglobin level, and physical work capacity of children was studied. Children from three rural schools studying from 4th to 7th standard were selected. One set of school children were given deworming tablet (400 mg albendezole) once in six months while the second school children received deworming tablet along with weekly dose of Iron Folic acid Tablet (60 mg of elemental iron and 0.5 mg folic acid). Anthropometric measurements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 6 publications
2
33
0
Order By: Relevance
“…For six comparisons which included iron or praziquantel, statistically significant effect sizes of 0.27 to 0.93 g/dL were found in four studies (Olds 1999, Taylor 2001, Bhoite 2012, Nga 2009,). These four studies also measured anthropometric outcomes, and found no effect of deworming on anthropometric outcomes (Olds 1999, Taylor 2001, Bhoite 2012 and Nga 2009).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…For six comparisons which included iron or praziquantel, statistically significant effect sizes of 0.27 to 0.93 g/dL were found in four studies (Olds 1999, Taylor 2001, Bhoite 2012, Nga 2009,). These four studies also measured anthropometric outcomes, and found no effect of deworming on anthropometric outcomes (Olds 1999, Taylor 2001, Bhoite 2012 and Nga 2009).…”
Section: Resultsmentioning
confidence: 96%
“…BMI was reported by five studies (Awasthi 2013, Bhoite 2012, Bobonis 2006, Monse 2013, Rozelle 2015). Mid‐upper arm circumference (MUAC) was reported by 11 studies (Dossa 2001, Nga 2009, Rousham 1994, Stephenson 1989, Stephenson 1993A, Greenberg 1981, Hadju 1997, Kloetzel 1982, Donnen 1998, Pust 1985, Watkins 1996).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations